풍력발전시스템의 전력변환부 3병렬 운전을 위한 LCL-필터 설계 - 윤동근 (The Graduate School, Ajou University, 2011)
Permanent Magnet Synchronous Generators (PMSG) are widely used in variable-speed wind turbines. However, the power devices must support high currents to get their high-power rating because the PMSG is connected directly to the grid through a back-to-back converter. Therefore, the rated current of the power device can be reduced to one third of the rated value by using a three-parallel operation. The low switching frequency of a high power system may cause an increase in the harmonics found in the output current. This paper proposes a design scheme for an LCL-filter used for three-parallel operation of a power converter in 2MW-wind turbines. An appropriate design method of the delta configured LCL-filter is also proposed to improve the output power quality in the system. A novel design method for the inner inductance of the LCL-filter is proposed in order to overcome the existing trial and error methods used in designing the filter. LCL-filters typically have a problem with a reduced power factor (PF), due to the capacitor used. To improve the poor PF, a simple compensation method is also proposed. The simulation and experimental results demonstrate that the grid current harmonics are low and the PF is improved.
학위논문(석사)--아주대학교 일반대학원 :전자공학과,2011. 2
Keywords: LCL필터; 풍력발전시스템; 역률보상; 3병렬